Sarcopenia: a potential cause and consequence of type 2 diabetes in Australia's ageing population?. Issue 7 (3rd October 2016) - Scott, David; de Courten, Barbora; Ebeling, Peter R
Summary: The incidence of type 2 diabetes is increasing in Australia's older adult population. Sarcopenia, the age‐related decline in skeletal muscle mass, quality and function, may make a significant but under‐appreciated contribution to increasing the risk of type 2 diabetes. As skeletal muscle is the largest insulin‐sensitive tissue in the body, low muscle mass in sarcopenia likely results in reduced capacity for glucose disposal. Age‐related declines in muscle quality, including increased mitochondrial dysfunction and fat infiltration, are also implicated in skeletal muscle inflammation and subsequent insulin resistance. Prospective studies have shown that low muscle mass and strength are associated with increased risk of incident type 2 diabetes. Prevalent type 2 diabetes also appears to exacerbate progression of sarcopenia in older adults. Recently developed operational definitions and the inclusion of sarcopenia in the International classification of diseases, 10th revision, clinical modification, provide impetus for clinicians to diagnose and treat sarcopenia in older patients. Simple assessments to diagnose sarcopenia can potentially play a role in primary and secondary prevention of type 2 diabetes in older patients. Lifestyle modification programs for older adults with type 2 diabetes, particularly for those with sarcopenia, should incorporate progressive resistance training, along with adequate intakes of protein and vitamin D, which may improve both functional and metabolic health and prevent undesirable decreases in muscle mass associated with weight loss interventions. As some older adults with type 2 diabetes have a poor response to exercise, clinicians must ensure that lifestyle modification programs are appropriately prescribed, regularly monitored and modified if necessary.